Language and Power - Fairclough, Norman, 1941- (London ; New York : Longman, 1989)
Language and Power is about how language works to maintain and change power relations in contemporary society, and how understanding these processes can enable people to resist and change them. Substantial changes in social life have taken place in the decade since the original publication, which have changed the nature of unequal power relations, and therefore the agenda for the critical study of language. In this second edition, Norman Fairclough brings the discussion completely up-to-date with the inclusion of a new chapter covering the 'globalisation' of power relations and the development of the internet in relation to language and power.
1- Introduction: critical language study --- 2- Discourse as social practice --- 3- Discourse and power --- 4- Discourse, common sense and ideology --- 5. Critical discourse analysis in practice: description --- 6- Critical discourse analysis in practice: interpretation, explanation and the position of the analyst --- 7- Creativity and struggle in discourse: the discourse of Thatcherism --- 8- Discourse in social change --- 9- Critical language study and social emancipation: language education in the schools.
Includes bibliographical references (p. [248]-252) and index.
Also issued online.
Keywords: Sociolinguistics; Discourse analysis -- Social aspects